World Economic Outlook, April 2011 : Tensions from the Two-Speed Recovery: Unemployment, Commodities, and Capital Flows. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2011)
The April 2011 edition of the World Economic Outlook assesses the global prospects for economic growth in the face of policy challenges that remain unaddressed and new challenges now coming to the fore.The recovery is gaining strength, but unemployment remains high in advanced economies, and new macroeconomic risks are building in emerging market economies. In advanced economies, the handoff from public to private demand is advancing, reducing concerns that diminishing fiscal policy support might cause a 'double-dip' recession. Financial conditions continue to improve, although they remain unusually fragile. In many emerging market economies, demand is robust and overheating is a growing policy concern. Rising food and commodities prices present new risks to the global economy. Two chapters directly explore these new challenges. Chapter 3 reviews the potential impact of oil scarcity on global growth, and Chapter 4 explores the potential response of international capital flows to changes in the global macroeconomic environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet